Minimum inhibitory concentration creep in Enterobacterales – A rising concern - Mondal, Soumyya; Mandal, Anwesha; Saha, Sipra; Partha Sarathi Chakrabarty; Das, Debalina (Asian Journal of Medical Sciences, 2024)
Background: The irrational use of antibiotics has led to the emergence of multidrug-resistant pathogens. The phenomenon of minimum inhibitory concentration (MIC) creeps occurs when organisms start showing raised MIC but within susceptible range giving an indication of the prevalence of rise in resistant pathogens in an area. Aims and Objectives: The aims and objectives of the study are to observe the susceptibility pattern among uropathogens and the possibility of MIC creeps among the Escherichia coli isolates sensitive to nitrofurantoin. Materials and Methods: This retrospective study was done in a tertiary care hospital in Kolkata to observe the susceptibility pattern among uropathogens and the possibility of MIC creeps. We took the data from all inpatient department and outpatient department patients sent for urine culture and sensitivity from October 1st, 2022, to September 30th, 2023. The antimicrobial susceptibility testing and MIC were conducted by VITEK Compact 2. The MIC of nitrofurantoin, one of the most widely used antibiotics for lower urinary tract infections, was calculated to investigate the phenomenon of MIC creep. All the statistical analyses were carried out using the Excel spreadsheet and OpenEpi version 3.01 platform. Results: In our study, a total of 631 urine samples were analyzed: 368 were positive with the most common isolate being E. coli (53%) followed by Klebsiella spp. (12%). Two percent of resistance was observed for fosfomycin and 8% for nitrofurantoin. Extended spectrum beta-lactamase (ESBL) producers E. coli was 127 (35%). Overall, 23/368 samples had a MIC ≥128 for nitrofurantoin. Among the ESBL producers, 13/127 had MIC ≥128 for nitrofurantoin. Conclusion: In the present study, it was observed that E. coli showed a reduced susceptibility for nitrofurantoin indicated by a creeping increase in MIC within normal range. Trends in rising MIC can be an alarming sign for using drugs such as nitrofurantoin judiciously. Antimicrobial stewardship practice should be strongly implemented in hospitals to curb rising resistance and for better prognosis of patients having infectious diseases.